Analysis of the sustainability of the Ecuadorian pension system, 2013-2025 - Contreras-Jaramillo, Mario Andrés (Papeles de Población, 2018)
The present investigation has as main objective to determine the amount of the retirement pension expenditure to be financed by payer during the period 2013-2025, taking as a variable incidence of the population factor to determine whether the Pension System of Ecuador is sustainable in the long term. In the first instance it is made a review of Social Security in a global context throughout history, later, it emphasizes the role of the same in Ecuador, of its pension system, Regulations (Social Security Act) and their characteristics. A brief conceptual and empirical review on demography, post this is used to quantify the future of pension expenditure, using for this purpose a projection model that considers the demographic factor, the evolution of the number of contributors and the evolution of the number of pensioners as relevant factors that determine both the coverage and the level of pensions in Ecuador. Finally, the main findings of the research, which will be used to understand current spending on pensions in Ecuador and, above all, help elucidate what might happen to the same in the future.